2017
DOI: 10.1080/16546628.2017.1361778
|View full text |Cite
|
Sign up to set email alerts
|

Dietary steamed wheat bran increases postprandial fat oxidation in association with a reduced blood glucose-dependent insulinotropic polypeptide response in mice

Abstract: Obesity is a global epidemic associated with a higher risk of cardiovascular disease and metabolic disorders, such as type 2 diabetes. Previous studies demonstrated that chronic feeding of steamed wheat bran (WB) decreases obesity. To clarify the underlying mechanism and the responsible component for the anti-obesity effects of steamed WB, we investigated the effects of dietary steamed WB and arabinoxylan on postprandial energy metabolism and blood variables. Overnight-fasted male C57BL/6J mice were fed an iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In order to investigate the effects of dietary steamed wheat bran and arabinoxylan on postprandial energy metabolism in mice, a group of researchers performed several experiments that included single feedings of a control diet vs. a steamed wheat bran diet and feeding a dietary fiber-free diet vs. different dietary concentrations of arabinoxylans. After feeding the arabinoxylan-enriched diet, a significantly lower peak level and AUC of postprandial glucose were seen when compared to the dietary fiber-free fed group ( 87 ). The results also showed lower postprandial blood GIP levels in the wheat bran fed group compared to the control diet-fed group.…”
Section: Discussionmentioning
confidence: 93%
“…In order to investigate the effects of dietary steamed wheat bran and arabinoxylan on postprandial energy metabolism in mice, a group of researchers performed several experiments that included single feedings of a control diet vs. a steamed wheat bran diet and feeding a dietary fiber-free diet vs. different dietary concentrations of arabinoxylans. After feeding the arabinoxylan-enriched diet, a significantly lower peak level and AUC of postprandial glucose were seen when compared to the dietary fiber-free fed group ( 87 ). The results also showed lower postprandial blood GIP levels in the wheat bran fed group compared to the control diet-fed group.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study of mice found that a single oral ingestion of WB decreases postprandial blood levels of glucose-dependent insulinotropic polypeptides and increases postprandial fat oxidation [20]. The extrapancreatic action of glucose-dependent insulinotropic polypeptides is to stimulate fat accumulation in the adipose tissue [21].…”
Section: Discussionmentioning
confidence: 99%
“…To understand the direct effects of extracellular glucose accumulation, a high glucose condition was established by pretreating the vascular tissues with high glucose-PSS (22.2 mM glucose in PSS) at 37 °C for 30 min, as previously reported by our laboratory [ 29 ]. These values were based on reported postprandial glucose levels in C57BL/6 J (~ 11.1 mM) and KKAy mice (~ 22.2 mM) in vivo [ 30 , 31 ]. The obtained change in vascular tension was shown as the generated tension per 1 mm length of the aortic ring.…”
Section: Methodsmentioning
confidence: 99%